A novel homozygous mutation of CFAP300 identified in a Chinese patient with primary ciliary dyskinesia and infertility - Zheng Zhou; Qi Qi; Wen-Hua Wang; Jie Dong; Juan-Juan Xu; Yu-Ming Feng; Zhi-Chuan Zou; Li Chen; Jin-Zhao Ma; Bing Yao (Asian Journal of Andrology)
Primary ciliary dyskinesia (PCD) is a clinically rare, genetically and phenotypically heterogeneous condition characterized by chronic respiratory tract infections, male infertility, tympanitis, and laterality abnormalities. PCD is typically resulted from variants in genes encoding assembly or structural proteins that are indispensable for the movement of motile cilia. Here, we identified a novel nonsense mutation, c.466G>T, in cilia- and flagella-associated protein 300 (CFAP300) resulting in a stop codon (p.Glu156*) through whole-exome sequencing (WES). The proband had a PCD phenotype with laterality defects and immotile sperm flagella displaying a combined loss of the inner dynein arm (IDA) and outer dynein arm (ODA). Bioinformatic programs predicted that the mutation is deleterious. Successful pregnancy was achieved through intracytoplasmic sperm injection (ICSI). Our results expand the spectrum of CFAP300 variants in PCD and provide reproductive guidance for infertile couples suffering from PCD caused by them.